Bank Guarantee as A Third Party in The Event of Default at PT. BNI (Persero), Tbk Market Branch Office Mayestik Jakarta - Yulia Mujiaty; Darma Wijaya; Deasy Novayanti; Siti Nurjanah; Prihatiningsih Prihatiningsih (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Bank Guarantee as Third Party Guarantee in the Event of Default at PT. BNI (Persero), Tbk Pasar Mayestik Branch Office, Jakarta Bank guarantee, is a payment guarantee given by the bank to a party in the form of a document. Default occurs when the obligation is not carried out or is negligent in the agreement between the creditor and the debtor. PT Bank State of Indonesia (Persero), Tbk. was founded as the central bank in Indonesia with the name